Antishivering effect of intrathecal versus intravenous tramadol in patients undergoing urethroscopic lithotripsy under spinal anesthesia - Manasa M; Jyoti Petkar; Dokku Kirtana; Karthik GS; Rangalakshmi S (Asian Journal of Medical Sciences, 2024)
Background: Shivering is the most common complication seen in the perioperative period in patients undergoing urological surgeries under spinal anesthesia. Intravenous tramadol is used for the treatment of shivering. Aims and Objectives: In this study, we wanted to assess the prophylactic effect of tramadol, intrathecal (IT) versus intravenous with the control group, in decreasing the incidence of shivering. Materials and Methods: Fifty-four eligible patients posted for urethroscopic lithotripsy (URSL) were randomly allocated into three equal groups – Group C: Received 2.5 mL 0.5% bupivacaine heavy + 0.5 mL normal saline intrathecally and 5 mL of normal saline intravenously, Group V: Received 2.5 mL of 0.5% bupivacaine heavy+0.5 mL normal saline intrathecally and 25 mg tramadol in 5 mL of normal saline intravenously, and Group T: Received 2.5 mL of 0.5% bupivacaine heavy + 25 mg (0.5 mL) of tramadol intrathecally and 5 mL of normal saline intravenously. The incidence and severity of shivering were noted. Onset of sensory and motor block, duration of post-operative analgesia, core body temperature, and adverse effects such as nausea, vomiting, and hypotension were noted. Results: The incidence of intraoperative shivering was significantly lower in Group T versus C (P=0.014) but comparable among Group I versus C (P=0.502) and Group T versus I (P=0.06). The duration of analgesia was significantly higher in Group T compared to Groups I and C (P<0.001). The additional tramadol requirement was significantly lower in Group T versus I and in Group T versus C but comparable among Group I versus C. Conclusion: The addition of 25 mg tramadol to IT 0.5% bupivacaine heavy is effective in preventing intraoperative shivering in patients undergoing urological surgeries like URSL.